Transactions of major housing stock. Dynamic market for rental flat portfolios. - Lorenz-Hennig, Karin; Held, Tobias (My University, 2013)
Nachdem Verkäufer und Investoren, aufgrund der Wirtschafts- und Finanzkrise, in den letzten Jahren ausgesprochen zurückhaltend im Bezug auf Transaktionen im Wohnungsbestand waren, ist der Markt seit 2011 wieder belebt. Diese Ausgabe stellt die aktuellen Verkaufszahlen des Jahres 2011 dar.

After sellers and investors, due to the economic and financial crises in the past years, were markedly reserved with respect to housing stock transactions, that market showed visible signs of movement again in 2011. This issue presents the current sales situation involving major housing stock in 2011.
Keywords: Wohnungswesen; Wohnungsmarkt; Wohnungsbestand; Wohnungswirtschaft; Immobilienmarkt; Wohnungsmarktbeobachtung